Peningkatan Kemampuan Menghitung Perkalian Melalui Pendekatan Kontekstual pada Siswa - Fadlia Mubakkira, Fadlia Mubakkira; Wilade, Surahman; Lapasere, Sisriawan; Pahriadi, Pahriadi (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to improve the multiplication calculation skills of grade III students of SDN 14 Balaesang through the application of a contextual approach. The research method used is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects in this study were 18 grade III students. The instruments used included student and teacher activity observation sheets, as well as formative tests at the end of each cycle. The results in cycle I, 12 students (66.7%) achieved completion, while in cycle II it increased to 15 students (83.3%). Student activity also increased from 71.25% in cycle I to 87.5% in cycle II. Teacher activity increased from 72.22% to 91.66%. The conclusion of the results of this study is that the application of a contextual approach can improve students' multiplication calculation skills and learning activities.   Keywords: Counting Ability, Multiplication, Contextual Approach, Classroom Action Research